Operational Performance of AKDP Route Network in Gorontalo: A Comparative Meta-Analysis Study of AKDP Route Network in Indonesia - Anton Kaharu,; Arrafi Himatul Gude,; Mohammad Yusuf Tuloli, (International Journal of Scientific Research in Science and Technology, 2024)
Public transportation is one of the important components in a regional transportation system. The intra-provincial city transportation (AKDP) routes in Gorontalo are the object of research in this study. This study aims to analyze the operational performance of AKDP routes in Gorontalo by considering several important variables, namely load factor, travel speed, headway, average waiting time, travel time, and frequency. This study also compares the results of the analysis with the results of the meta-analysis of the operational performance of public transportation in Indonesia. The results of the study are expected to provide insight for improving the public transportation system, especially in Gorontalo, as well as provide recommendations for more efficient and sustainable transportation policies.
Keywords: AKDP Route; Operational Performance; Load Factor; Travel Speed; Intermediate Time; Waiting Time; Travel Time; Frequency; Meta-Analysis